Access to employee assistance programs and employee wellbeing: a cross-sectional study of employees in Southeast Asia - Amani Fadzlina Abdul Aziz; Tiffanie Ong (BMC Public Health)
Abstract Background The average person spends 1/3 of their lives working. However, approximately 15% of working adults worldwide are struggling with a mental disorder at any given time. The COVID-19 pandemic has spearheaded the importance of employee mental health, highlighting the role that employers can play in preserving employee wellbeing. Although Employee Assistance Programs (EAPs) are slowly becoming an established practice, it is still a relatively new phenomenon in most of Asia. This study therefore aims to investigate the prevalence of employees in the Southeast Asian region who have access to EAPs and understand the relationship between EAP access and employee wellbeing. Methods This cross-sectional, online survey-based study involved 15,302 employees from Malaysia, Singapore, Philippines, Thailand, Indonesia, and Vietnam who completed the Depression, Anxiety, Stress Scales (DASS-21), Thriving from Work Questionnaire (TfWQ), and sociodemographic measures. Employee productivity and turnover intention was also measured as a secondary outcome. Hierarchical regression models were conducted to determine the influence of EAP access on employee wellbeing. Subgroup analyses were conducted on employees with access to EAPs to explore how different forms of EAP services contribute to employee wellbeing. Results Only 29.04% of employees in the region reported being aware of having access to any forms of EAP services provided by their employers. After controlling for sociodemographic variables, access to EAP was significantly associated with improved mental health, thriving, and productivity, and reduced turnover intention (p < 0.001) among employees in the region. Subgroup analyses revealed that employees had access to well-being and mental health webinars, talks, or workshops (12.64%), followed by sponsored counselling, therapy or carelines (11.16%). Access to regular mental health risk assessment and screening was the form of EAP service significantly associated with the highest number of outcomes. Conclusion Having access to EAP services alone is associated with improved employee wellbeing outcomes. However, different forms of EAP services can vary in their impact on employee wellbeing. Our findings suggest a need to improve accessibility and diversity of EAP offerings for employees in Southeast Asia post-pandemic.